(untitled) (Sustainability in Debate, 2023)
The agricultural sector has a low representation in the Brazilian energy mix and in terms of distributed generation systems installed in rural areas. However, this sector represents a large portion of the gross domestic product. This work proposes an approach for identifying the driving factors for inserting mini and micro distributed generation systems in the agricultural sector. A methodology was developed based on a territorial approach, using indicators in Piauí to determine the major factors that drive its installation. It is observed that the main driving factor for rural microsystems is the total irrigated area of agricultural establishments. As for mini rural systems, the main driving factor is the average area of agricultural enterprises. In addition, it is reasonable to state that the proposed methodology applies to other states, from a regional and national perspective, as well as to other types of consumers.